Flent: The FLExible Network Tester - Høiland-Jørgensen, Toke; Augusto Grazia, Carlo; Hurtig, Per; Brunstrom, Anna (Karlstad University, 2018)
This is the experimental dataset from the paper "Flent: The FLExible Network Tester" published at the ValueTools 2017 conference.

Also published at: https://www.cs.kau.se/tohojo/flent/
Keywords: Computer Sciences; Datavetenskap (datalogi)